Synopsis: How big are post-harvest losses? Evidence from teff - Minten, Bart; Engida, Ermias; Tamru, Seneshaw (International Food Policy Research Institute, 2016)
Based on a unique large-scale data set on teff production and marketing, Ethiopia’s most important cash crop, we study post-harvest losses in rural-urban value chains, specifically between producers and urban retailers in the capital, Addis Ababa. We analyze the structure of the value chain and rely on self-reported losses by different value chain agents (farmers, wholesale traders, and retailers). We estimate that post-harvest losses in the most prevalent pathway in the rural-urban value chain, amount to between 2.2 and 3.3 percent of total harvested quantities. The variation in this figure depends on the storage facilities used and on assumed losses during transport at the farm. These losses are significantly lower than is commonly assumed for staple foods, possibly because of the rather good storage characteristics of teff due to its low moisture content. These findings, nonetheless, point to the need to gather further solid evidence on post-harvest losses in staple foods in these settings to ensure appropriate policies and investments